The Efforts of Islamic Religious Education Teachers in Shaping Students' Religious Morals at State Junior High School 43, West Tanjung Jabung - Dewi Susana; Yudi Kurniawan (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study aims to examine the efforts of Islamic Religious Education (PAI) teachers in shaping students’ religious character, identify supporting and inhibiting factors, and determine solutions to overcome the obstacles at SMP Negeri 43 Tanjung Jabung Barat. This research employs a descriptive qualitative method, with data collected through observation, interviews, and documentation. Data analysis techniques include data reduction, data display, and conclusion drawing. The findings reveal that teachers’ efforts in shaping students’ religious character are carried out through exemplary behavior, habituation of religious activities, advice, guidance, and the application of reward and punishment systems. Supporting factors include parental support, student motivation, teacher commitment, and school facilities. Meanwhile, inhibiting factors include family background, peer influence, limited facilities, and the impact of social media. The solutions implemented involve strengthening collaboration between schools and parents, enhancing supervision, and continuously instilling religious values.